Work and psychological well-being - Daniels, Kevin (Henry Stewart Talks, 2012)
Impact of well-being and stress, Describing well-being, Classic approaches to job design, stress and well-being, Policy and management implications of classic approaches to job design, Limitations of approaches to measurement, Importance of individual differences, Changing and fluid nature of work, Goals, stress and well-being, Cognition, stress and well-being, Using job resources for coping and self-regulation, Implications of cognitive and agency based approaches to jobs, stress and well-being for policy and practice